The Effect of Duolingo on l2 Learners’ Pronunciation: Vowel Analysis through Minimal Pairs - Giedrė Balčytytė; Viktorija Skerstonaitė (Jaunųjų Mokslininkų Darbai)
The present paper focuses on the acoustic analysis of Russian speakers’ English vowel production before and after using the Duolingo application. The study aims to investigate phonetic acquisition of English vowels, particularly in the context of minimal pairs. The method chosen to achieve this objective is experimental analysis using phonetic acoustic variables – formant frequencies (F1 and F2) and vowel duration which were evaluated through spectrograms. Ten Russian-speaking volunteers participated in the experiment and were treated pre-test and post-tests. The results observed in this experiment show that Duolingo application contributed to Russian speakers’ production of tense/lax English vowel pairs /u/-/ʊ/ and /i/-/ɪ/ with F1 and F2 frequency values closer to those of British English, but no improvements were seen with the open front vowel /æ/. The duration of vowels did not see significant improvements apart from the vowel pair /u/-/ʊ/.